1993
DOI: 10.1177/009365093020003004
|View full text |Cite
|
Sign up to set email alerts
|

Agenda-Setting Effects of Television News Coverage and the Effects Decay Curve

Abstract: Some fundamental concepts in agenda-setting are related to a simple cognitive memory decay process. Accounting for issue obtrusiveness and amounts of prior coverage, predictions for the size of the relationship between declining accumulated television coverage and issue salience are derived. Levels of declining accumulated coverage are estimated by applying an exponential decay function to the prominence of daily television coverage. This function presumably models simple forgetting of coverage that occurs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 24 publications
2
61
0
3
Order By: Relevance
“…Previous research that found that average recall of non-urgent news stories is limited to 12-60 days [39], suggesting that this matching of news and survey data was sufficient.…”
Section: Newspaper Coverage Of Secondhand Smoke Issuesmentioning
confidence: 89%
“…Previous research that found that average recall of non-urgent news stories is limited to 12-60 days [39], suggesting that this matching of news and survey data was sufficient.…”
Section: Newspaper Coverage Of Secondhand Smoke Issuesmentioning
confidence: 89%
“…The AP is a wire service that is used by more than 85% of U.S. newspapers (Fan & Tims, 1989;Watt, Mazza, & Snyder, 1993) and is a reasonable proxy for broader media coverage of news topics (Fan, 1988;Romantan, 2004). The Lexis-Nexis database was used to search for cancer AP articles.…”
Section: Identification Of Cancer News Articlesmentioning
confidence: 99%
“…Understanding news coverage is an important part of understanding public perceptions of health topics-particularly those for which people may have little personal experience [34]. According to a 1989 Robert Wood Johnson Foundation survey, mainstream news media are the primary public source for information about mental illness [33].…”
Section: The Media's Role In Constructing Public Discoursementioning
confidence: 99%